The Influence of User Generated Content (UGC) on Increasing Visitors to the Lampung Community Hub - Dian Septiana; Maya Zahwa Aulia; Prima Rini Metri Oktavia (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the effect of User Generated Content (UGC) on increasing visitor numbers at the Lampung Community Hub, particularly in the context of digital participatory communication and Electronic Word of Mouth (e-WOM). Research Methodology: This study employs a quantitative approach to examine the influence of UGC on visitor growth. Data were collected through surveys of Community Hub visitors and analyzed using statistical techniques to measure the relationships between UGC exposure, trust formation, visit intention, and visitor sustainability. Results: The findings indicate that UGC significantly contributes to increasing visitor numbers through five primary mechanisms: (1) enhanced digital exposure and visibility of the community hub, (2) increased public trust through authentic user experiences, (3) collective validation as social proof, (4) strengthened visit intention, and (5) promotion of repeat visits or sustainability. Conclusions: UGC functions as a highly persuasive digital communication instrument that effectively enhances visitor occupancy and fosters loyalty at community hubs. Its participatory nature strengthens credibility and engagement within the digital ecosystem. Limitations: This study focused on a single Community Hub in Lampung, which may limit the generalizability of the findings to other regions or organizational contexts. Additionally, this study primarily examined digital interaction variables without exploring offline influencing factors. Contributions: This study contributes to the literature on digital communication and community engagement by demonstrating the strategic role of UGC in increasing visitor occupancy and loyalty. It also provides practical implications for Community Hub managers to integrate structured UGC management strategies to optimize public engagement and sustainability.